Impacts of Climate Change on Human Health: Emerging evidence and call to action - Jemilah, Mahmood *; Guinto, Renzo R * (Penerbit Universiti Sains Malaysia, 2022)
It is already widely known that the climate crisis is an existential threat that is already impacting every aspect of human society and the planet. Hence, action from all sectors is not only necessary but urgent. One area that requires immediate attention is the impact of climate change on human health. For the past three decades, there have been numerous efforts from the academic and policy worlds to highlight the immutable connection between human health and climate change. However, it was only during the 26th Conference of Parties (COP26) of the United Nations Framework Convention on Climate Change, which was held in November 2021 in Glasgow, Scotland, that health started to receive an appropriate level of attention, in large part due to the still-ongoing Coronavirus disease (COVID-19) pandemic. Under the leadership of the World Health Organization (WHO) a two week series of activities and discussions was held, bringing together health professionals, researchers, policymakers and advocates to highlight the importance of health in the climate discourse. The COP26 health programme culminated with more than 50 countries making a commitment to build climate-smart national health systems that are both resilient to the growing impacts of climate change and sustainable, so that they do no further harm to the planet through carbon emissions and other types of pollution (1). We hope that Malaysia will join in this global campaign.